Menakar Transaksi Leasing dalam Tinjauan Hukum Ekonomi Syariah - Sumadi Sumadi (Jurnal Ilmiah Ekonomi Islam, 2018)
This study aims to measure the lease transaction in the review of sharia economic law. The phenomenon of the practice of leasing transactions in economic activities that develop today is a complicated and complicated issue. Because of its emergence as one of muamalah practices involving a number of parties initially known in advance by the Western world and not found the discussion specifically in the classic books and fatwa ulama. This type of research is a qualitative research using literature study method as the methodology of completion. With the object of research Leasing case seen from the point of view of Islamic economic law, and how the Islamic economy to answer the problem. Leasing Transactions are financing activities in the form of provision of capital goods (eg cars or factory machinery) paid for a certain period of time on a regular basis. From result of research obtained result that related with lease transaction. The form of leasing activity is divided into two, namely the operating lease (ie, lease without option) and financial lease (lease with option rights) Operating lease in fiqih terms equals ijara, while the financial lease practice which has been adjusted to syara criteria 'is called al -The Objective of Muntahia bit Tamlik (IMBT) and the law is halal, while based on the practice and reality in daily life, financial lease shows transaction prohibition, and scholars agree that there is in practice financial lease (conventional leasing)